KONFLIK POLITIK PADA MASA KHALIFAH USTMAN BIN AFFAN - Dahlan Dahlan (AL-ILMU, 2022)
The problem of political conflict began to occur during the reign of Caliph Ustman bin Affan. Because before this third caliphate political problems were fine because the previous caliphs had extraordinary achievements in the development of Islam. Both in terms of economy, culture, regional expansion, social, religious and other things that we cannot mention one by one. Then the question arises. Is this all the work of Ustman bin Affan. In fact, Uthman bin Affan was a very generous, shy, and even humble person, because behind this he was used by his relatives to occupy all government positions during his caliphate. The political conflict that occurred because Uthman bin Affan gave crucial positions to his relatives. Therefore, there was a rebellion from friends. After the death of Ustman bin Affan, a greater upheaval began. Because the relatives of Uthman bin Affan wanted the next caliph to try Uthman's killer. It should be noted for all that the political conflicts that occurred during the caliphate of Uthman bin Affan were not due to Uthman's favoritism towards his brothers. But the greed of relatives who want to control all lines of government.